SHORT-TERM OVERREACTION OF ISLAMIC STOCKS TO SPECIFIC EVENTS IN INDONESIA - Sofina Mujadiddah; Noer Azam Achsani; Mohammad Iqbal Irfany (Bank Indonesia, 2020)
Overreaction is a phenomenon caused by stock market inefficiencies and also a reaction to certain events. Das and Krishnakumar (2016) explain that some overreaction phenomena violate the theory of capital market efficiency. As experienced by other stocks , Islamic stocks also probably experience market inefficiencies. This study aims to analyse the phenomenon of overreaction in Islamic stocks, as well as the factors that influence the phenomenon, by using a two-stage testing method: two paired sampling and cross-sectional regression. Two specific events which occurred in 2016-2018, and which were followed by price reversal and return reversal, are studied. The results show that the election of Donald Trump as US President (Event 1) and the bombings in Surabaya (Event 2) were significant in the overreaction in the winner stock category. The factors that influenced the two events were different. The overreaction to Trump’s election proved to be significantly influenced by information leakage, while the bombings in Surabaya significantly affected the company ownership category . The results indicate that Islamic stocks continue to have several transactions which are prohibited by the DSN MUI fatwa in the short term.